1994
DOI: 10.1016/0891-0618(94)90010-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic, peptidergic and GABAergic innervation of the ventrolateral and dorsolateral motor nuclei in the cat S1/S2 segments: An immunofluorescence study

Abstract: Indirect single- and double-staining immunofluorescence techniques were used to study the serotoninergic, peptidergic and GABAergic innervation of the ventrolateral (Onuf's nucleus) and dorsolateral (innervating intrinsic foot sole muscles) nuclei, located in the S1/S2 segments of the cat spinal cord. The relative density of 5-hydroxytryptamine-, thyrotropin-releasing hormone-, substance P- and gamma-aminobutyric acid-immunoreactive axonal varicosities was similar in both nuclei. The highest relative density w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…1d, L1, 8C) (Krukoff et al, 1985). 8D) Arvidsson et al, 1990;Ramirez-Leon et al, 1994). At all levels of the spinal cord, dense networks of immunolabeled fibers, a number of which were large varicose, were visualized in layer I (marginal zone; Fig.…”
Section: Distribution Of Nerve Fibersmentioning
confidence: 94%
“…1d, L1, 8C) (Krukoff et al, 1985). 8D) Arvidsson et al, 1990;Ramirez-Leon et al, 1994). At all levels of the spinal cord, dense networks of immunolabeled fibers, a number of which were large varicose, were visualized in layer I (marginal zone; Fig.…”
Section: Distribution Of Nerve Fibersmentioning
confidence: 94%
“…The majority of them make contact with ␥-amino butyric acid (GABA)-immunoreactive dendrites or somata (Blok et al, 1997a). Other studies have indicated that many of the local neurons projecting to the Onuf 's nucleus are located in the sacral DGC (Konishi et al, 1985;Nadelhaft and Vera, 1996) and that Onuf 's nucleus receives a substantial afferent input from GABAimmunoreactive neurons in the caudal lumbar and sacral cord (Ramirez-Léon et al, 1994). Electrical stimulation in the sacral DGC results in a sharp decrease in the intraurethral pressure indicating a relaxation of the external urethral sphincter (Blok et al, 1998b).…”
Section: Medial Regionmentioning
confidence: 98%
“…We, therefore, used serotonin as a marker of direct supraspinal projections to DL (Ramirez-Leon et al, 1994;Tang et al, 1998). Previous studies in our laboratory and the work of others have established that serotonin immunoreactivity distal to the injury site is a good indicator of both SCI severity and the degree of recovery of somatic sensorimotor function (Faden et al, 1988;Wrathall et al, 1994;Teng and Wrathall, 1997).…”
Section: Role Of Supraspinal Projections In Detrusor-eus Coordinationmentioning
confidence: 99%